Pengaruh Motivasi Kerja, Budaya Organisasi, Dan Kualitas Kehidupan Kerja Terhadap Kinerja Karyawan (Studi Pada Dinas Perumahan Dan Kawasan Permukiman (Disperkim) Kab.Bondowoso) - Farah Nauliana; Siti Asiyah; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to examine the effect of work motivation, organizational culture, and quality of work life on employee performance (study at the Department of Housing and Settlement Areas (DISPERKIM) Bondowoso Regency). the population in this study were employees who were registered as civil servants at the Bondowoso Regency Housing and Settlement Area (DISPERKIM). The analysis technique used is multiple linear regression analysis. based on the results of the study showed that motivation, organizational culture, and quality of work life simultaneously had a positive and significant effect on employee performance at the Department of Housing and Settlement Areas (DISPERKIM) Kab. Bondowoso. Work motivation has no significant effect on employee performance at the Department of Housing and Settlement Areas (DISPERKIM) Kab. Bondowoso. Organizational culture has a significant effect on employee performance at the Department of Housing and Settlement Areas (DISPERKIM) Kab. Bondowoso. Quality of work life has a significant effect on employee performance at the Department of Housing and Settlement Areas (DISPERKIM) Kab. Bondowoso. keywords: work motivation, organizational culture, quality of work life, employee performance